Analisis Struktur Biaya dan Profitabilitas Usaha Ikan Golden Denisoni (Sahyadria denisonii) di Azzam Aquari, Bojong Rangkas, Kabupaten Bogor, Jawa Barat - Astari, Belinda; Vinasyiam, Apriana; Setiawati, Afina Darojah; Melani, Astrid; Dewi, Cindy Faticha Permata; Syafiq, Hafiz; Amelia, Junita Putri; Rukmana, Nanda (Universitas Batangahari Jambi, 2026)
Golden Denisoni (Sahyadria denisonii) is one of the most valuable freshwater ornamental fish commodities with strong prospects in the international niche market. This species is widely demanded due to its attractive coloration, premium mutation strains, and limited number of consistent producers. This writing was developed based on interview notes with Mr. Wisnu, the manager of a golden denisoni farming business located in Bogor Regency, West Java. Information was collected through direct discussions regarding the history of the business, breeding and rearing activities, market demand, operational resources, cost components, and constraints faced during cultivation. The results indicate that the largest demand comes from export markets, particularly China, where buyers seek high-quality clear fish for ornamental trade. The selling price of clear 2-inch golden denisoni ranges from IDR 20,000 to 25,000 per individual, reflecting the high economic value of this commodity. Key farming activities include mutation breeding, juvenile rearing, daily water exchange, and intensive aeration to prevent ammonia accumulation and maintain dissolved oxygen levels. Major challenges encountered in production are fungal infections, environmental stress, and fish mortality caused by human error in farm monitoring. The collected information was structured using the business model canvas framework, covering customer segments, value propositions, distribution channels, customer relationships, key activities, key resources, partnerships, cost structure, and revenue streams. Overall, golden denisoni farming demonstrates significant profitability potential as a premium ornamental aquaculture business. Sustainable growth of this sector requires consistent water quality management, improved operational control, and strengthened market partnerships to ensure stable production and continuous export supply.